PENGUATAN KEMANDIRIAN LOKAL DENGAN MEMBANGUAN PARTISIPASI LEMBAGA MASYARAKAT DI DESA - H. Abdul Rasul (AkMen JURNAL ILMIAH, 2015)
The Village government is service nature front unit to society with is principal pillar for success all programs. Therefore, brace village be a necessity can not be postponed in the effort to speed up materialized society welfare as region autonomy aim.